How media content influences economic expectations: Evidence from a global expert survey - Boumans, Dorine; Müller, Henrik; Sauer, Stefan (Journal of forecasting, 2023)
This article sheds light on the impact of the media on economists' expectations for future economic developments. We conducted a worldwide economic expert survey and find that the media provides most economists with valuable information that influences their expectations. This applies significantly more for economists in countries with long standing democratic systems and developing countries with somewhat flawed democratic institutions than for economists in newer democracies and countries with authoritarian regimes. Moreover, the experts estimate the influence of the media remarkably higher on others than on themselves. This is consistent with the theory of the third‐person effect that says that an individual's behavior is influenced due to the belief that other people find certain issues important and act accordingly.